Gender Performance, Gender Identity and Stigma in the Life of Cosplayers in Malang City - Putri M, Dita Wahyu; Kholifah, Siti; Rahmawati, Intan (Komunitas, 2021)
The purpose of this study was to examine gender performance, gender identity and gender stigma experienced by cosplayers in Malang City. Gender performance that occurs repeatedly in a certain period of time is able to create a gender identity. Gender identity is perpetuated based on the repetition of gender performance in the lives of cosplayers. In his life, a cosplayer has gender differences in his life. There are gender differences when they become cosplayers and when they are in their social life. The existence of differences made by a cosplayer raises a problem. The problem experienced by cosplayers is stigma. Stigma is often experienced by cosplayers who have two genders in their lives. Gender changes that keep repeating make people accuse that a cosplayer is not a normal person. The intended abnormality leads to the sexuality of a cosplayer. The research method used in this study is phenomenology with the data generated is a description of the cosplayer's experience in playing her gender, forming her gender identity to the stigma attached to her body. Collecting data by means of observation, interviews and documentation. The result of this research is that a cosplayer's gender identity is formed based on continuous repetition. Gender performance is one of the processes of gender identity formation. The gender performance that is displayed is from imitating the character or character he likes. Gender performance is the cause of cosplayers getting stigma from their social environment. The stigma attached to this cosplayer then crosses gender in the form of sexual deviation.